Achievable Rate Analysis for Massive MIMO Base Stations with One-Bit ADCs - Mollén, Christopher (Linköping University, 2016)
MATLAB files for the computation of numerical achievable rates of the uplink of a massive MIMO system, where the base station quantizes the received signals with one-bit ADCs.

The dataset was originally published in DiVA and moved to SND in 2024.

MATLAB files for the computation of numerical achievable rates of the uplink of a massive MIMO system, where the base station quantizes the received signals with one-bit ADCs.

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
Achievable Rate Analysis for Massive MIMO Base Stations with One-Bit ADCs
Keywords: communication; kommunikation; systems; system; Communication Systems; Kommunikationssystem